Association of the polymorphism of the Toll-like receptor (TLR)-3 and TLR-9 genes with hepatitis C virus-specific cell-mediated immunity outcomes among Egyptian health-care workers. (2nd October 2020) - Abdelwahab, S F; Hamdy, S; Osman, A M; Zakaria, Z A; Galal, I; Sobhy, M; Hashem, M; Allam, W R; Abdel-Samiee, M; Rewisha, E; Waked, I
Summary: Variations in the immune response could explain resistance to hepatitis C virus (HCV) infection. Toll-like receptor gene (TLR)-3 is an innate detector of dsRNA viruses, and the TLR-9 gene recognizes bacterial and viral unmethylated cytosine–phosphate–guanosine (CpG) motifs. We previously reported that the TLR-3.rs3775290 CC genotype was associated with HCV chronicity and that the TLR-9 gene played no major role in this infection. This study identified the role of TLR-3.rs3775290 (c.1377C/T), TLR-9.rs5743836 (−1237T→C) and TLR-9.rs352140 (G2848A) gene polymorphisms in predicting the outcome of HCV-specific cell-mediated immunity (CMI) among Egyptian health-care workers (HCWs). We enrolled 265 HCWs in this study and divided them into four groups. Group 1: 140 seronegative-aviraemic HCWs; group 2: 20 seronegative-viraemic HCWs; group 3: 35 subjects with spontaneously resolved HCV infection; and group 4: 70 chronic HCV HCWs (patients). All subjects were genotyped by polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) analysis for the TLR-3.rs3775290, TLR-9.rs5743836 and TLR-9.rs352140 single nucleotide polymorphisms (SNPs). We also quantified HCV-specific CMI in the four groups using an interferon (IFN)-γ enzyme-linked immunospot (ELISPOT) assay in response to nine HCV genotype 4a, overlapping 15mer peptide pools covering the whole viral genome. No statistically significant difference was found between CMI-responding subjects with different HCV states and TLR-3.rs3775290 or TLR-9.rs352140 genotypes. However, there was a significant relationship between the outcome of the HCV-specific CMI and the TLR-9.rs5743836 genotype among the responding subjects ( P  = 0·005) and the chronic HCV patients ( P  = 0·044). In conclusion, TLR-9.rs5743836 SNP, but not TLR-3.rs3775290 or TLR-9.rs352140 genotypes, could predict the outcome of HCV-specific CMI responses among Egyptians infected with genotype-4. Graphical Abstract: